AKTIVITAS ANTIJAMUR MINYAK ATSIRI RIMPANG DRINGO (Acorus calamus L.) TERHADAP JAMUR Botryodiplodia theobromae PENYEBAB BUSUK BUAH PISANG - N. L. Rustini (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
A compound with antifungal activity has been isolated from dringo (Acorus calamus L.) essential oil. Steamdistillation was conducted to isolate the oil and resulted in 0.5 % yield. Antifungal activity test towardsBotryodiplodia theobromae showed that the ethanol posseses antifungal activity with an inhibition capacity of 94.4%. GC-MS analysis resulted in three main peaks at 15.008; 15.233; and 16.490 minutes. It was suggested from thepeak intensity that the last peak represents the major component of the extract. Futher more according to the librarydata base, the spectra of this compound matches with the Asarone spectra.